Critiques of Disparities: Revising the Mainstream Narratives for the Alternative Relations in Wide Sargasso Sea, Foe and A Tempest - Khanal, Niran (The Harvest, 2025)
This paper aims to study the textual relations regarding the role of ideologies for the maintenance of center-margin relations. My efforts are to uncover the problems related to race, gender and nationality in the discourses of the mainstream texts, and observe the connections between such problems and counter-discursive narrations of the contesting texts. I argue that beside aesthetics, the mainstream texts have political and ideological orientations that serve the interests of the privileged. That is why the alternative writers critique them for the social transformation and justice to the suppressed underclass people and other excluded groups. The new literary discourses emerge from the limitations of the previous discourses. So, epistemology gets the new direction by the disruptive narratives which are constructed with the vision of alternative relations. In this study, I employ the comparative approach to examine the intertextual relations between the pairs of texts with regard to the influence of ideologies in the construction of social hierarchies in the mainstream narratives. The finding of this paper is that the alternative narratives, written from the perspectives of the marginalized, emerge from the ideological fault lines of the hegemonic discourses of the mainstream narratives. The alternative narratives: Aime Cesaire’s A Tempest, Jean Rhys’s Wide Sargasso Sea and JM Coetzee’s Foe critique the mainstream narratives: William Shakespeare’s The Tempest, Charlotte Bronte’s Jane Eyre and Daniel Defoe’s Robinson Crusoe respectively. The critical authors attempt to uncover the suppressed voices of the marginal by reconfiguring the canonical literary discourses. Their attempts are to articulate voices for the justice of socially excluded and underprivileged.